2015
DOI: 10.1016/j.jri.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating interleukin-17 levels in preeclampsia

Abstract: Increasing evidence suggests that an exaggerated maternal systemic inflammatory response, as well as an angiogenic imbalance plays a central role in the pathogenesis of preeclampsia. In this study, we determined circulating levels of interleukin-17 (IL-17) along with those of angiogenic factors in healthy non-pregnant and pregnant women and preeclamptic patients, and examined whether serum IL-17 levels of preeclamptic patients were related to their clinical features and angiogenic factor concentrations. Fifty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 31 publications
(18 reference statements)
10
42
0
1
Order By: Relevance
“…The sFlt-1/PlGF ratio can be modulated by not only sFlt-1, but also PlGF. The present observation that plasma levels of PlGF are decreased in RUPP vs Preg rats is consistent with reports that PlGF levels are decreased in preeclamptic women [29, 33, 36] and in RUPP and Dahl salt-sensitive rat models of HTN-Preg [17, 24, 80, 82]. 2) Because plasma angiogenic factors represent the global release from different maternal tissues, we measured the angiogenic factors in the different regions of the uterus and found that sFlt-1 was increased, PlGF was decreased and sFlt-1/PlGF was increased in the placenta and uterus of proximal, middle and distal regions of the RUPP uterus compared to the corresponding regions in the Preg uterus.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The sFlt-1/PlGF ratio can be modulated by not only sFlt-1, but also PlGF. The present observation that plasma levels of PlGF are decreased in RUPP vs Preg rats is consistent with reports that PlGF levels are decreased in preeclamptic women [29, 33, 36] and in RUPP and Dahl salt-sensitive rat models of HTN-Preg [17, 24, 80, 82]. 2) Because plasma angiogenic factors represent the global release from different maternal tissues, we measured the angiogenic factors in the different regions of the uterus and found that sFlt-1 was increased, PlGF was decreased and sFlt-1/PlGF was increased in the placenta and uterus of proximal, middle and distal regions of the RUPP uterus compared to the corresponding regions in the Preg uterus.…”
Section: Discussionsupporting
confidence: 93%
“…Angiogenic imbalance could play a role in the observed regional changes in placental and fetal growth, uteroplacental vascularization and MMPs in the Preg and RUPP uterus because: 1) The levels of sFlt-1 and the sFlt-1/PlGF ratio increased in the plasma of RUPP vs Preg rats. The observed increases in plasma sFlt-1 levels and sFlt-1/PlGF ratio in RUPP rats are consistent with reports that circulating sFlt-1 and the sFlt-1/PlGF ratio are elevated in preeclamptic women [29, 33, 35, 36, 77], and in RUPP and other animal models of HTN-Preg [17, 24, 7882]. The sFlt-1/PlGF ratio can be modulated by not only sFlt-1, but also PlGF.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…sFlt-1 gene is localized on chromossome 13q12, and an extra copy of this gene in women with trisomy 13 may lead to excess circulating sFlt-1, reduced PlGF and increased risk of PE (Kakigano et al, 2013). Several reports have shown higher circulating levels of sFlt-1 in early and late PE (Tsatsaris et al, 2003; Ramma et al, 2012; Bian et al, 2015; March et al, 2015; Molvarec et al, 2015; Tuzcu et al, 2015). Serum sFlt-1 is also higher in women with previous PE (~0.5 ng/mL) than in women with previous normal pregnancy (~0.3 ng/mL), even 6 months or more after delivery (Tuzcu et al, 2015).…”
Section: Circulating Bioactive Factors In Preeclampsiamentioning
confidence: 97%
“…PlGF levels during 21 and 22 weeks of gestation are ~353 pg/mL, rising steadily during gestation to reach a median level of ~574 pg/mL after 29 and 30 weeks of gestation (Krauss et al, 2004). During PE, circulating PlGF levels decrease (Tsatsaris et al, 2003; Ramma et al, 2012; Bian et al, 2015; Molvarec et al, 2015) and the decrease is more apparent in early than late PE (March et al, 2015). PlGF has four alternatively spliced mRNA species (PIGF 1–4), and its predominant isoform PIGF-1 is downregulated in PE (Bates, 2011).…”
Section: Circulating Bioactive Factors In Preeclampsiamentioning
confidence: 99%